The effectiveness of using animation media to improve mathematical logic intelligence - Sarah, Siti; Ahmasi, Latif Al; Saudah; Isa, Muhammad (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
Mathematics is the main subject. Mathematics solves many problems in many fields, namely biology, physics, chemistry, astronomy, calculus, statistics, computer programming, and others. However, many students often consider mathematics as a complex subject. One of the reasons is that students are not trained to include mathematics the problem-solving process. Mathematical, logical intelligence is the ability to solve aproblem by mathematics. Living in the 21st century demands the use of technology in almost all aspects of life. This study aims to determine the effectiveness of animation media in improving the mathematical logic intelligence of fifth-grade students at an elementary school with 37 students. The research method is a quasi-experiment with a control-group pretest-posttest design. Research instruments in the form of tests and documents. Data analysis techniques using t-test and N-Gain calculation. The results showed that using animation media to learn mathematics effectively improves mathematical logic intelligence. It is evidenced by the experimental class N-Gain score of 69% with a reasonably practical category, which is higher than the control class N-Gain score of 52% with a less effective category. The t-test results show a difference in mathematical logic intelligence between students who learn using animation media and those who do not, with a significance value smaller than 0.050, namely 0.036. This research will inform that mathematical logic intelligence can be carried out using animation media. The other researcher can continue the research by finding the mathematical logic intelligence indicator that contributed the most to mathematics learning activity.